Energy-Aware Routing in Wireless Sensor Networks Using Local Betweenness Centrality - Xiao-Hui Li; Zhi-Hong Guan (International Journal of Distributed Sensor Networks)
We propose an energy-aware dynamic routing strategy in order to provide balanced energy consumption in wireless sensor networks, hence, prolonging the lifetime of the network. The proposed routing algorithm uses local betweenness centrality to estimate the energy consumption of the neighboring nodes around a given local sensor node, without requiring global information about the network topology or energy consumption, and to divert traffic from nodes that are more heavily used. Because nodes with large local betweenness centrality consume energy more quickly, the network lifetime can be prolonged by redistributing energy consumption to nodes with smaller local betweenness centrality. Simulation results showed that the proposed routing strategy has advantages over shortest path routing with respect to extending network lifetime and balancing energy consumption in wireless sensor networks, yet does not introduce significant additional transmission overhead or a longer average path length.